Peranan Analisis Regresi Untuk Analisis Wilayah Dan Analisis Geografi = The Role of Regression Analysis in Regional and - Kartiman Kudonarpodo (Majalah Geografi Indonesia, 1988)
Regression analysis is a subset of the major group of multivariate analysis which is well-known in statistical analysis. Geographical analysis in general and regional analysis in particular frequently rely on multivariate analysis to study the interrelationship of spatially distributed variables within a region. Regression analysis is applied to investigate mutual correlations between one dependent variable and one or a set of independent variables. Computation of regression analysis is difficult to carry out by hand and the calculations increase tremendously with the number of variables and investigated cases. With the present availability of micro-computers and complete statistical software packages, regression analysis poses no longer a problem to the investigator. Relieved of computations problems, the investigator may pay his attention now fully to the selection and quality assessment of the variables entered into the analysis.